Pathophysiology of cancer cachexia - Younes,Riad N. (2000)
Cancer cachexia is a frequent complication observed in patients with malignant tumors. Although several decades have passed since the first focus on the metabolic dysfunction's associated with cancer, few effective therapeutic interventions have been successfully introduced into the medical armamentarium. The present study thoroughly reviews the basic pathophysiology of cancer cachexia and the treatment options already investigated in that field. Experimental and clinical studies were evaluated individually in order to clarify the intricate alterations observed in tumor-bearing patients. The difficulties in introducing sound and effective nutritional support or metabolic manipulation to reverse cancer cachexia are outlined in this review.